Acute immune responses in zebrafish and evasive behavior of a parasite – who is winning? - Mathiessen, Heidi; Kjeldgaard-Nintemann, Sebastian; Gonzalez, Carlota Marola Fernandez; Henard, Cyril; Reimer, Julie Algreen; Gelskov, Sara Vebæk; Marana, Moonika Haahr; Jørgensen, Louise von Gersdorff (Frontiers in Cellular and Infection Microbiology, 2023)
The protozoan parasite Ichthyophthirius multifiliis is an economically important parasite for the aquaculture- and ornamental fish industry. The parasite is abundant worldwide and infects the skin, gills and fins of freshwater fish species. For approximately the last fifty years the innate and protective immune mechanisms induced by I. multifiliis have been in focus in different fish hosts. By utilizing transgenic zebrafish, new tools to investigate this have emerged. The aim of this study was therefore to elucidate early immune responses in zebrafish larvae by using gene expression and in vivo imaging of neutrophil and macrophage behavior during infection. For the first time, zebrafish larvae were infected with the parasite and infection dynamics, parasite size and host-parasite interactions were investigated. Results showed that the larvae responded with mild inflammation and that the 12 compared to 5 days post fertilization larvae were significantly less susceptible. It was furthermore observed that neutrophils and macrophages were attracted to the parasites and that neutrophils reacted with neutrophil extracellular traps (NETs) when fighting the parasite. The parasite was rotating vigorously, presumably to impede the neutrophils and macrophages from attaching to it but on rare occasions, neutrophils and macrophages were able to kill the parasite. Based on these observations, we concluded that the parasite uses the rotation as an immune evasive strategy and that the zebrafish larvae respond with high activity from neutrophils and macrophages locally but systemically only with mild inflammation.